Tensões induzidas por descargas atmosféricas indiretas em linhas de distribuição compactas trifásicas - Larissa Lorrany Pacífico Lima (2023)
In recent decades, it has been verified in several Brazilian states the replacement of conventional medium-voltage distribution lines for compact lines. Compact distribution lines use dielectric-coated phase conductors, separated by polymeric spacers sustained by a bare steel cable called messenger. Depending on the grounding philosophy adopted by the utility, it is possible to use a periodically grounded neutral conductor together with the messenger cable. This is the case of the compact distribution lines installed in the CEMIG-D concession area, which therefore have two multigrounded wires in addition to the phase conductors. Despite this remarkable feature, there are no studies evaluating how the presence of two periodically grounded conductors and their grounding characteristics could change the response of compact lines to voltages induced by nearby lightning strikes. In addition, the insulating layer covering the phase conductors of compact lines modifies fundamental parameters necessary for the calculation of transient overvoltages. However, it is usual to disregard the presence of the insulating layer when calculating the effects of lightning on compact lines. Therefore, it is also the aim of this work to assess the limits of this approximation. To evaluate the response of compact lines to the effects of indirect lightning, computational models are used to describe the channel-base current waveform, the return-stroke current propagation along the channel, the electromagnetic fields generated by the return-stroke current, the coupling of these fields with the line and the computational solution of the resulting electromagnetic transients. The performed analyzes consider a compact three-phase distribution line, including or not the presence of the neutral conductor or the insulating layer on the phase conductors. It is shown that the natural presence of the neutral conductor together with the messenger cable causes a reduction on lightning-induced voltages on compact distribution lines. It is also shown that the phase conductors of compact lines can be represented as bare cables in lightning induced voltage calculations.